Avaliação da transmissão da imunidade passiva e efeitos fisiopatológicos frente a infecção experimental primária e desafio de cordeiros com Haemonchus placei e H. contortus - Reiniger, Regina Celis Pereira (2012)
The aim of this study was to evaluate the effect of the transfer of passive immunity and pathophysiological effects against experimental Haemonchus placei or H. contortus primary infection and challenge. The first experiment evaluated the transmission of passive immunity in parasite-free lambs. At 6-month old, lambs were divided in three groups: infected with H. contortus (Hc), with H. placei (Hp) and uninfected (C for control), and challenged at 9-month old when lambs were again divided in four groups: Hc-Hc, Hc-Hp, Hp-Hc and C-C. Serological analyses showed the transfer of anti-H. contortus IgG, but with a gradual decline over time in both females and lambs. During primary infection, faecal egg count (FEC) average was twice for the Hc group compared to Hp (p <0.0001). The Hc group presented the lowest packed cell volume compared to the other groups (p <0.0001). Primo-infected sheep with either H. placei or H. contortus did not develop resistance when challenged with same species- or across-species parasite. Single 5,000 L3 dose experimental infection was not sufficient to cause clinical signs, nor to rise and maintain anti-H. contortus IgG levels in the infected animals. There is passive transfer of anti-H. contortus IgG for lambs through the colostrum, however the IgG levels begin a gradual decrease from day 30 after birth.